(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
From the intrinsic limits of §§. 39-42 of the work Being and Time, this research paper seeks to thematize the Selfhood of Dasein understood as a non-thingness wisdom of self, the which is correlative of the existentiality and facticity of this entity. This searching is carried out from the mode of appearing of existential Care, precisely this existential word is responsible for endowing of unit and / or structural totality to the constitutive moments of the being-in-the-world as such. This analysis also is exercised in order to enhance a possible link between Care and Selfhood, where, as it seems, the Selfhood is constituted as a neccesary and sufficient condition of Care. This Selfhood is responsable for not only to favor the unity of Care, but the transition from impropriety to existential property of Dasein.